The Role of Audio Visual Media in Supporting English Pronounciation: A Qualitative Study - Giawa, Nurul Hikmah; Dwi Putri Juwita Zebua; Adriani Putri Hura; Henti Sartika Sari Gulo; Anjelina Agustina Ndruru; Inayah Syah Putri Telaumbanua; Yaredi Waruwu (Edu-Ling: Journal of English Education and Linguistics, 2025)
This study explores students' experiences and perceptions of using audio-visual media in supporting their pronounciation skills. A qualitative descriptive design is used to captures detailed and nuanced insights into participants’ experiences. Ten undergraduate students majoring in English Education were purposefully selected as participants to provide in-depth perspectives. Data were gathered through semi-structured interviews, which encouraged open discussions while addressing themes closely aligned with the research objectives. This study reveals that students commonly use YouTube videos, language learning apps like Duolingo, and movies or TV shows as audio visual media to practice pronunciation. They also employ techniques such as mimicking native speakers, shadowing, and recording and playback to refine their speech. As a result, students report noticeable improvements in articulation, clarity, intonation, and fluency. The combination of exposure to authentic speech patterns, feedback, and consistent practice enables students to enhance their pronunciation, gain confidence in speaking, and communicate more naturally. These findings underscore the value of integrating audio-visual media into pronunciation practice for English learners.